The Influence of Emotional Intelligence on Turnover Intention Through Job Satisfaction As A Mediating Variable Among Employees of PT. Mabhakti - Ni Made Astri Padmayani; Ni Wayan Mujiati (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Employee turnover intention remains one of the pressing challenges for organizations striving to maintain workforce stability. This study investigates how emotional intelligence influences employees’ intention to leave, with job satisfaction positioned as a mediating factor. Grounded in the Traditional Turnover Theory, the research was conducted at PT. Mabhakti, located at Jl. Nangka No. 29, Dangin Puri Kaja, North Denpasar, Bali, Indonesia. The study involved a total of 40 employees, all of whom were included as respondents using a census or saturated sampling approach. Data collection was carried out through structured interviews and questionnaires, and the analysis was performed using path analysis via SPSS. The findings reveal that emotional intelligence negatively and significantly affects turnover intention, while it positively and significantly influences job satisfaction. Additionally, job satisfaction itself negatively affects turnover intention and plays a significant mediating role in the relationship between emotional intelligence and turnover intention. These outcomes reinforce the Traditional Turnover Theory, highlighting that emotionally intelligent employees are more likely to experience internal positive drivers—such as self-motivation and emotional resilience—that contribute to job satisfaction and, consequently, a reduced desire to leave. The study underscores the importance of fostering emotional intelligence and enhancing job satisfaction as strategic approaches to curbing turnover intention and promoting organizational stability and productivity.